Current Trends in Game-Based Learning - Marques, Margarida Morais; Pombo, Lúcia (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
A myriad of technological options can be used to support digital game-based learning. One popular technology in this context is the mobile device, considering its high penetration rate in our societies, even among young people. These can be combined with other technologies, such as Augmented Reality (AR) or Virtual Reality (VR), to increase students' motivation and engagement in learning processes.Due to this, there is an emergent need to know and promote good practices in the development and implementation of game-based learning approaches in educational settings. This was the motto for the proposal of the Education Sciences (ISSN: 2227-7102) Special Issue "Current Trends in Game-Based Learning". This book is a reprint of this Special Issue, collecting a set of five papers that illustrate the contribution of innovative approaches to education, specifically the ones exploring the motivational factors associated with playing games and the technology that may support them.